Emotions and teaching styles among academics: the mediating role of research and teaching efficacy. Issue 3 (16th March 2019) - Zhang, Li-fang; Fu, Mingchen; Li, Dorothy Tao; He, Yunfeng
Abstract: The key purpose of this research was to investigate the mediating role of academics' self-efficacy in teaching and research (termed 'academic self-efficacy') in the relationship between emotions in teaching and teaching styles. Two hundred and thirty-two academics from 13 higher educational institutions in Shanghai, mainland China, responded to three self-report inventories, each assessing academics' emotions in teaching, efficacy in teaching and research, and teaching styles, respectively. Results showed that academics' emotions in teaching statistically predicted teaching styles, both directly and indirectly – through academic self-efficacy. Findings have enriched the literature on emotions in teaching, that on teaching styles, and that on teacher/academic self-efficacy. Practical implications are proposed in relation to academics and university senior managers.